An Information System Operation Model for Curriculum Management in Supply Chain for National Skills Standards in Thailand - Chansamut, Artaphon (International Journal of Supply Chain Management, 2022)
The main purpose of paper is to design and and evaluate an information system operation model for curriculum management in supply chain for  national skills standards in Thailand. The research method is divided into 7 steps namely Analyze and synthesize documents and research literature both within and outside the country ,Use the obtained data to establish the conceptual frameworks  ,To present a model ,To create questionnaire for evaluating the suitability of the model ,Develop a questionnaire and determine the weight of the score ,Data collection and analysis . Ten expert from higher education institutions in supply chain and information technology were included in the research as sample group. Data analysis was the average mean and standard deviation. The model development process has 5 components manly namely, Suppliers, Manufacturers, Service provider, customers and consumer.The  modeldevelops to support sustainable information system. As the overall model was shown at the high level, Experts agreed the model.